Regional resilience to displacements: Explaining the regional capacity to re-employ displaced workers - Kristina Nyström (European Regional Science Association (ERSA), 2015)
Job displacement, which is defined as an involuntary loss of job due to economic downturns or structural changes, hit millions of workers each year. According to OECD (2013) 2-7 percent of workers are displaced every year. For Sweden, OECD (2013) reports an average displacement rate of about 2 percent for the period 2000-2008. Our knowledge on the individual consequences of displacement, in terms of, for example, unemployment duration, and earning losses is comprehensive (See e.g. Hammermesh 1989 and OECD (2013). However, knowledge about regional differences in patterns of displacements and regional resilience to displacements is still limited. For instance, Eliasson and Storrie (2006) note that prior to their study knowledge about regional patterns of Swedish displacements is primarily based on case studies. Using individual-firm level data from all firms and regions in Sweden Nyström and Viklund Ros, (2014) shows that displacement rates and the regional ability to re-allocate competence after a business closure varies substantially. This paper intends contribute to the knowledge about the regional resilience to business closures. The term resilience refers to the ability adapt to a chock incurred by, for example, business closures. In this paper I intend to study which regional characteristics that influence the regional resilience to displacements. Which regional characteristics influence if displaced employees quickly are re-employed in other industries and businesses? In this paper it is argued that the regional environment in terms of i) the characteristics of regional closures, ii) the characteristics of the individuals in the region, iii) characteristics of the regional industry and iv) the characteristics of the regional economy influence the regional resilience to displacements in terms of the ability to re-employ displaced employees. The characteristics of regional closures, refers to, for example, the regional share of closures and the size of the closures. The characteristics of the individuals in the region refer to, for example, the competence in terms of education, age structure and share of individuals with immigrant background in the region. Characteristics of the regional industry refers to the unrelated and related industry variety (Frenken et al 2007 and Boschma et. al 2012) and the industry structure in terms of the share of the manufacturing industry and service sectors. Finally, the characteristics of the regional economy refer to, for example, the size of the region, unemployment level and industrial turbulence in terms of entry and exit rates. In the empirical part of the paper a unique dataset of matched firm-employees enable us to study the regional patterns of re-employment of displaced workers in 81 Swedish regions 2001-2009. For policymakers understanding how the re-employment process after displacements differs across regions should be valuable knowledge.
Keywords: J6; R1; 330; Displacements; exit. Labor mobility; regional development